The improvement of Hovenia acerba-sorghum co-fermentation in terms of microbial diversity, functional ingredients, and volatile flavor components during Baijiu fermentation - Zhang, Jing; Zhao, Minhui; Chen, Jing; Zhu, Yuanting; Xiao, Chen; Li, Qi; Weng, Xiaoqi; Duan, Yunxuan; Zuo, Yong (Frontiers in Microbiology, 2024)
The quality of Baijiu was largely affected by raw materials, which determine the flavor and taste. In the present study, organic acids, polyphenols, volatile flavor components and microbial community in Hovenia acerba-sorghum co-fermented Baijiu (JP1) and pure sorghum-fermented Baijiu (JP2) were comprehensively analyzed. Organic acids, polyphenols and volatile flavor components in JP1 were more abundant than JP2. The abundance and diversity of bacteria and fungi in JP1 was higher than that in JP2 in the early stage of fermentation, but presented opposite trend in the middle and late stages. Leuconostoc, Lentilactobacillus and Issatchenkia were dominant genera in JP1. Whereas, Cronobacter, Pediococcus and Saccharomyces occupied the main position in JP2. Lentilactobacillus and Issatchenkia were positively related to most of organic acids and polyphenols. Pseudomonas, Rhodococcus, Cronobacter, Pediococcus, Brucella, Lentilactobacillus, Lactobacillus, Saccharomycopsis, Wickerhamomyces, Aspergillus, Thermomyces and unclassified_f__Dipodascaccae were associated with the main volatile flavor components. The main metabolic pathways in two JPs exhibited the variation trend of first decreasing and then increasing, and the metabolism activity in JP1 were higher than that in JP2. This study identified the key microorganisms and discussed their effect on organic acids, polyphenols and volatile flavor components during the fermentation of Baijiu with different raw materials, providing a scientific basis for the development and production of high-quality Baijiu.